1990
DOI: 10.1111/j.1439-0329.1990.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

An intersterility group of Heterobasidion annosum specialized to Abies alba

Abstract: A third intersterility group of//, annosum in Europe has been identified from Italy. It is specialized to Abies alba, and hence is called the F (fir) group. It is closely related to the European S group, but is sexually incompatible with the geographically adjacent S population occurring in the Alps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
2

Year Published

1993
1993
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 8 publications
4
97
0
2
Order By: Relevance
“…The intersterility group of each isolate was determined with the aid of mating tests using two homokaryotic testers from each of the groups S, P and F (Capretti et al, 1990).…”
Section: Fungal Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The intersterility group of each isolate was determined with the aid of mating tests using two homokaryotic testers from each of the groups S, P and F (Capretti et al, 1990).…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…The high susceptibility of silver fir to H. annosum was thought to be related to environmental and climatic conditions prevailing in Italian territories (Biraghi, 1962;Moriondo, 1970). Later studies, however, pointed more to the variability of the fungus (Moriondo et al, 1988), and subsequent mating experiments demonstrated that the fungus infecting silver fir formed an intersterility group (F group) of its own (Capretti et al, 1990). Subsequently, F group isolates were found in other parts of Europe including France, Switzerland, Austria, Slovenia, Poland, Hungary, Bulgaria and Greece Capretti et al, 1994;Munda, 1994;Pagony & Szántó, 1995;Lakomy, 1996;Tsopelas & Korhonen, 1996;Capretti & La Porta, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spruce (S), Pine (P) and Fir (F) (Korhonen, 1978;Capretti et al, 1990). A putatively non-outcrossing, non-pathogenic population referred to as Heterobasidion araucariae occurs in the southern hemisphere (Korhonen, 1978;Chase, Ullrich & Korhonen, 1985;Buchanan, 1988).…”
mentioning
confidence: 99%
“…Our focus was on isolates from silver fir, because there is already a good record of S ISG isolates from Norway spruce (Picea abies (L.) Karst.) in all of the alpine areas studied by us (Capretti et al 1990. Both stumps and sympto-matic or dead trees were sampled.…”
Section: Methodsmentioning
confidence: 99%